Translanguaging as an Inclusive Pedagogical Practice in Early Education Classes - Driouch, Aziz (International Journal of Language and Literary Studies, 2022)
Using students’ full linguistic resources in classes has always been controversial. Some researchers still adopt the monolingual ideology, while others see that incorporating students’ L1s can help in many aspects of teaching practices. This has led to several multilingual pedagogical practices, one of which is translanguaging. The latter has been theorized as a pedagogical resource for building and promoting students’ knowledge and inclusion. This study examines translanguaging as an inclusive strategy in early education. The participants are teachers and students from three preschool classes. This study aims to explore to what extent translanguaging helps engage students more in their classroom activities and boosts their well-being in their classes. Then, teachers’ perceptions of translanguaging as a pedagogical practice were investigated. Both classroom observations and interviews were used as research instruments in this study. The results indicated that translanguaging helps significantly in engaging young learners in their classroom activities and increases participation and fun during learning activities. Concerning the teachers’ perceptions, although they see that translanguaging creates more fun and engagement, they are still reluctant to embrace and employ it in their daily teaching practice for various pedagogical and personal reasons.